PENGARUH PROFITABILITAS, LEVERAGE,CORPORATE GOVERNANCE,DAN SALES GROWTH TERHADAP TAX AVOIDANCE PADA PERUSAHAAN MAKANAN DAN MIUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2019-2023 - Chania, Fitriyanti; Putra, Ramdani Bayu; Dewi, Rindy Citra (Journal of Information Systems Management and Digital Business, 2025)
This study aims to examine the influence of profitability, leverage, corporate governance, and sales growth on tax avoidance in food and beverage companies listed on the Indonesia Stock Exchange (IDX) during the period of 2019-2023. Tax avoidance has become a significant issue for companies as it relates to the strategic management of taxes to minimize tax liabilities, while maintaining compliance with legal requirements. Profitability, leverage, corporate governance, and sales growth are key financial and managerial variables that may affect tax avoidance practices. Using a sample of food and beverage companies from the IDX, this research employs multiple regression analysis to analyze the relationships between the independent variables and tax avoidance. The results of this study are expected to provide valuable insights for policymakers, regulators, and company management in managing tax-related decisions and corporate governance practices in the context of the Indonesian food and beverage industry.keyword: Profitabilitas, Leverage, Corporate Governance, Sales Growth, Tax Avoidance